Making Work Sustainable in Business and Social Enterprises - Furmańska-Maruszak, Agnieszka; Sudolska, Agata (Olsztyn Economic Journal, 2017)
The aim of this paper is identification of the activities supporting the implementation of a sustainable work concept both in firms and social enterprises operating in Poland. The paper focuses on activities with regards to the quality of the job and work environment, improving employee health, safety and well-being, introducing flexible hours, developing employee skills and reconciling working and non-working life. Moreover, the paper is an attempt to identify the components of an organization’s philosophy favorable to innovations that mostly support the implementation of the sustainable work concept. The research findings presented in the paper prove that firms are focused mainly on introducing new solutions related to employee health and safety as well as social and living condition improvement. On the other hand, social enterprises are more active in implementing the solutions enabling employee reconciliation between work and personal life. The paper also presents the correlation coefficients between chosen components of an organization’s philosophy favorable to innovations and the need for introducing solutions oriented toward a sustainable work concept. The research findings point out the importance of making innovation management the central element of organizational strategy. The second important component of an organization’s philosophy relates to focusing on positive relations between employees, both at the organizational level and in teams. Additionally, in the case of social enterprises, the paper highlights the importance of involving people undergoing the reintegration process in creating innovations.